PREDICTING THE REVENUE AND EXPENDITURE OF INDIA POST: A TIME SERIES MODEL - Lekshmi G, Minu; Maheswari M, Uma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India Post, an organization with a significant historical role in communication and financial inclusion in India, faces challenges in today's technology-driven communication landscape. It competes against private logistics companies and banking institutions in a highly competitive environment. To stay relevant, India Post has introduced innovative schemes and technology-supported services. However, financial profitability remains a concern. The current research aims to analyse revenue and expenditure trends over the past five years and make forecasts for the next five years. The analysis is made with the help Power Bi and the forecasting is made with 95 per cent confidence level. From the trends and forecasts, It is seen that although banking services have been profitable, their revenue is expected to decline, necessitating measures to enhance their performance. Efforts should also focus on increasing revenue from money orders and postal orders. While revenue from postage is stable but largely uncertain, investments in this area should be scaled down. Additionally, the sale of stamps generates limited revenue, demanding cost-cutting initiatives. Operating expenses are consistently increasing, prompting the need to optimize them through cost-effective alternatives and employee cross-training. Raising awareness about cost-consciousness among postal employees can further contribute to reducing expenses. By efficiently managing costs, India Post can strive towards improving its financial prospects.